2015
DOI: 10.1007/s12892-014-0083-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cucumber mycorrhiza inoculation under low and high root temperature grown on hydroponic conditions

Abstract: Cucumber is a subtropical vegetable sensitive to high and low root temperature. Additionally, mycorrhiza with beneficial effect on plant growth can increase plant tolerance to stress. This experiment was carried out as a factorial design based on CRD to study the effect of mycorrhiza density (0, 1,000 spores and 2,000 spores) on cucumber (Cucumis sativus cv. Super N3) under low (15°C), high (35°C), and optimum (25°C) temperature root zones. The result showed that low and high root zone temperatures decreased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In vegetables, AM inoculation has found to increase the yield by enhanced biomass production ( Haghighi et al, 2015 , Duc et al, 2018 ). AM inoculation also plays a significant role in uptake of higher amount of nutrients, leaf water potential and stomatal conductance ( Khan et al, 2013 ).…”
Section: Thermal (Heat and Cold) Tolerance By Am Inoculation In Vegetmentioning
confidence: 99%
See 1 more Smart Citation
“…In vegetables, AM inoculation has found to increase the yield by enhanced biomass production ( Haghighi et al, 2015 , Duc et al, 2018 ). AM inoculation also plays a significant role in uptake of higher amount of nutrients, leaf water potential and stomatal conductance ( Khan et al, 2013 ).…”
Section: Thermal (Heat and Cold) Tolerance By Am Inoculation In Vegetmentioning
confidence: 99%
“…It has also found to raise the enzymatic activity in the plants, activation of antioxidant defense mechanisms and accumulation of protecting molecules so as to reduce cell membrane damages ( Liu et al, 2016 , Caradonia et al, 2019 , Pasbani et al, 2020 ). There are several reporting of increased vegetable yield on inoculation of plants with arbuscular mycorrhiza ( Chen et al, 2013 , Liu et al, 2014 , Haghighi et al, 2015 ). Several studies claim that different vegetables inoculated with AMF grow better than non-AM fungi inoculated vegetation under the cold climatic conditions.…”
Section: Thermal (Heat and Cold) Tolerance By Am Inoculation In Vegetmentioning
confidence: 99%
“…Unlike in this study, when exposed to low or high RZTs, Korean mint (Agastache rugosa L.) exhibited significantly lower fresh and dry root weight due to temperature stress (Lam et al, 2020). In a study with cucumber cultivar Super N3, Haghighi et al (2015) found that 25 C was ideal for increasing dry root weight because lower and higher temperatures caused stress on the plants. Al-Rawahy et al (2019) found that cooled RZTs of 22 and 25 C produced significantly more leaves than the 28 C treatment or the 33 C control in cucumber 'Reema F1', once again stressing the importance of optimal temperature to produce better yield is dependent on crop and cultivar.…”
Section: Discussionmentioning
confidence: 99%
“…AMF improve the absorption and translocation of mineral nutrients thanks to their ability to reach beyond the rhizosphere, which is reflected in the growth and development of the melon plants and other Cucurbitaceae [35]. Nevertheless, the TFW parameter did not show significant differences between treatments.…”
Section: Effects Of Amf Colonization On Host Speciesmentioning
confidence: 95%